Insertion of cuff inflation line into pediatric tracheal tubes related to oral and nasal tracheal intubation depth. Issue 6 (24th March 2021) - Kemper, Michael; Fischer, Martina; Grass, Beate; Dave, Mital H.; Weiss, Markus
Abstract: Background: In clinical practice, the cuff inflation line of cuffed pediatric tracheal tubes often interferes with securing tracheal tubes. Methods: The insertion site of the cuff inflation lines and the lengths of four different brands and nine sizes of commonly used cuffed pediatric tracheal tubes were measured and compared in vitro with oral and nasotracheal intubation depths as calculated by different formulas for pediatric patients aged from birth to 16 years. Motoyama's recommendation was used for age‐related size selection of cuffed pediatric tracheal tubes. Results: The proportion of the distance from the tracheal tube tip to the insertion site of the cuff inflation line varied considerably between the tracheal tubes (Microcuff: 48.5–60.7%; Parker: 48.7–73.2%; Ruesch: 59.1–77.8%; and Shiley: 46.0–60.3%). Using different formulas for oral or nasotracheal intubation depth, the insertion site of the cuff inflation line was placed within the oral or nasal cavity or within an area 1 cm beyond the teeth or the nostrils in almost all tracheal tubes tested. Positioning the insertion site 2 cm from the proximal end of the tracheal tubes resulted in a cuff line–free tube area of ≥1 cm in all orally and almost in all nasally inserted tracheal tubes, considering maximum recommended tracheal intubation depths. Conclusion: The cuff inflation line in almost all commonly used cuffed pediatric tracheal tubes interferes with securing the tracheal tube due to its insertion site into the tracheal tube. This potentially carries the risk of kinking, obstruction, or damage to the cuff inflation line with ensuing failure to deflate or inflate the cuff. The proposed position of the insertion of the cuff inflation line 2 cm from the proximal end of the tracheal tube would ensure a 1‐cm‐wide cuff line–free circular area beyond the oral or nasal cavity in nearly all assessed tracheal tube sizes.